The extent of achieving ease of use in educational websites: an analytical study of the website of the Deanship of E-Learning and Distance Education at King Abdulaziz University | مدى تحقيق سهولة الاستخدام في المواقع التعليمية: دراسة تحليلية لموقع عمادة التعلم الإلكتروني والتعليم عن بعد في جامعة الملك عبد العزيز - Al Malki | المالكي, Modi Bent Mohamed | موضي بنت محمد (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
This study investigated the extent to which ease of use was achieved on the Deanship of Learning website Electronic and distance education at King Abdulaziz University, and despite the increase in the number Educational websites for universities and the increase in the number of users, we find a shortage - especially in... The Arab world - in studies that are concerned with measuring the extent of achieving ease of use for users These sites discuss or discuss the architecture of the information they contain in accordance with the latest international standards | تناولت هذه الدراسة التعرف على مدى تحقيق سهولة الًاستخدام لموقع عمادة التعلم الإلكتروني والتعليم عن بُعد في جامعة الملك عبد العزيز، وعلى الرغم من زيادة عدد المواقع التعليمية للجامعات وزيادة عدد المستخدمين لها، نجد نقصا -وخصوصا في العالم العربي- في الدراسات التي تهتم بقياس مدى تحقيق سهولة الًاستخدام لمستخدمي هذه المواقع أو تناقش معمارية المعلومات التي تحتويها وفق أحدث المعايير العالمية